THE EFFECT OF EDIBLE COATING OF TONGUE LEAVES (Aloe vera) ON THE QUALITY AND SAVING TIME OF LOHMANN BROWN CHICKEN EGGS - R. A., Christanto; Okarini, I. A.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
This study aims to determine the effect of aloe vera ( A lo e vera ) extract edible coating on the quality of Lohman Brown chicken eggs during storage. This research was conducted on Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University, lasted for 30 days. The research design used was, completely randomized design (RAL) within the study period of 10, 20, and 30 days, with 4 treatments and 3 replications, each of which was carried out as many as 3 eggs of Lohman Brown chicken. Each treatment required 36 items and each replication consisted of 3 items. So that the number of eggs used in this study was 108 eggs. The variables observed were storage time to decrease egg weight (%), shelf life of haugh unit (HU), shelf life of egg yolk color, shelf life of egg pH, and shelf life of egg yolk index (IKT). The data obtained were analyzed using ANOVA and Duncan's test. The results of this study can be concluded that the aleovera coating was stored at room temperature 27 ? -28 ?. The treatment of C1 (100% aleovera), C2 (50% A lo e vera + 10ml aquades), C3 (50% A lo e vera + 10ml aquades), and C0 (without coating ) on ?? Lohman Brown chicken eggs had a significant effect (P <0.05) on variables shelf life against haugh unit (HU), shelf life of egg yolk color, shelf life of egg pH, shelf life of egg yolk index (IKT), and no significant effect (P> 0.05) on storage time variable on weight loss eggs (%) storage time of 10, 20, and 30 days, respectively. Key words: chicken eggs, edible coating, Alo e vera, shelf life